O professor iniciante de língua inglesa e a influência do mentor na construção de seus conhecimentos profissionais - Nieves, Maria Rosario Garcia (2017)
This research, of exploratory matter in its essence, takes part of the discussion of professional development of beginning English teachers and the construction of professional knowledge, connected to teaching. Based on studies by Carlos Marcelo-Garcia, Maria da Graça Mizukami and Lee Shulman, among others, the main objective was to analyze the mentor¿s influence on the professional development and of the construction of knowledge essential to teaching. In order to achieve it, the main objective was broken down into the following specific ones: a) to identify a profile of the beginning English teacher as well as their first professional destination; b) to identify and analyze the different kinds of knowledge found in the practice of beginning English teachers and c) to investigate possible influences of mentoring their teaching practice. First steps of research included bibliographic and literature research and empirical data were collected through exploratory questionnaires, released on social media groups related to English Language Teaching. Quantitative data were analyzed by their results in numbers and data originated from open questions were analyzed following aspects of the Discourse of the Collective Subject theory, which were applied to key-questions related to the specific objects. Results provided profiles of Beginning English Teachers, the influence of undergraduate teacher training programs in their practice and the positive impacts of Mentoring, either by mentors or more experienced peers, such as empowerement in the classroom, on the construction and development of Professional Knowledge related to Teaching English, such as the fusion of Specific Content Knowledge with Pedagocical Knowledge, creating Pedagogical Knowledge of English Language Teaching.